2018
DOI: 10.1016/j.chemosphere.2017.10.061
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal exposure to deltamethrin reduces the abilities of giant water bugs to prey upon Aedes aegypti larvae

Abstract: Freshwater ecosystems provide environmental conditions for many arthropod species, including pests like mosquitoes and beneficial insects. Giant water bugs, Belostoma anurum (Hemiptera: Belostomatidae), are aquatic insects that provide biological control of mosquitoes and small vertebrates in freshwater environments. However, the application of insecticides aiming to control mosquitoes can lead to insecticide exposures of aquatic predators that can result in their death or significant reductions in their behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 46 publications
0
7
0
1
Order By: Relevance
“…The repellence mechanism of action of the C. alba extract against A. aegypti could be explained by the direct interactions of its constituents with the AaegOBP1 receptor. Regarding the correlations between the binding mode and repellence, it is generally hypothesized that repellence activity is related to longer docking times for molecules interacting with the internal pocket regions, compared to other molecules in the external region [ 62 ]. In addition to DEET presenting a binding site at the center of a long hydrophobic tunnel [ 63 ], this hypothesis was also verified for another phytochemical, lapachol, which has been shown to be responsible for the repellent activity of Tabebuia heptaphylla extracts [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The repellence mechanism of action of the C. alba extract against A. aegypti could be explained by the direct interactions of its constituents with the AaegOBP1 receptor. Regarding the correlations between the binding mode and repellence, it is generally hypothesized that repellence activity is related to longer docking times for molecules interacting with the internal pocket regions, compared to other molecules in the external region [ 62 ]. In addition to DEET presenting a binding site at the center of a long hydrophobic tunnel [ 63 ], this hypothesis was also verified for another phytochemical, lapachol, which has been shown to be responsible for the repellent activity of Tabebuia heptaphylla extracts [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that mosquito larvicides can impair key behavioral parameters in aquatic predators, such as locomotion and prey catching, leading to unsuccessful foraging (Gutiérrez et al 2017b;Valbon et al 2018;Lajmanovich et al 2019). Interestingly, at low and intermediate prey densities, backswimmers that were previously exposed to pyriproxyfen preyed on a higher number of mosquito larvae than unexposed insects (i.e., soon after pyriproxyfen exposure).…”
Section: Discussionmentioning
confidence: 99%
“…Warren 2000; McCauley and Rowe 2010).Our results for the survival abilities of B. amnigenus under such scenario, i.e., facing a 24h pyriproxyfen exposure and placed under non-contaminated environment, revealed that backswimmers did not show any difference in their survival abilities when compared to those pyriproxyfen-unexposed predators.Recent studies have reported that mosquito larvicides can impair key behavioral parameters in aquatic predators, such as locomotion and prey catching, leading to unsuccessful foraging(Gutiérrez et al 2017b;Valbon et al 2018;Lajmanovich et al 2019). Interestingly, at low and intermediate prey densities, backswimmers that were previously exposed to pyriproxyfen preyed on a higher number of mosquito larvae than unexposed insects (i.e., soon after pyriproxyfen exposure).…”
mentioning
confidence: 99%
“…Relyea and Hoverman ( 2008 ) showed that Belostoma flumineum predation on tadpoles decreased with increased malathion concentration, most probably because of decreased prey activity and decreased capture ability of the water bug. Sublethal deltamethrin application decreased the predatory efficiency of Belostoma anurum significantly on Aedes aegypti larvae (Valbon et al, 2018 ). The predatory efficiency of Buenoa sp.…”
Section: Methodsmentioning
confidence: 99%